2015
DOI: 10.1038/tpj.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of tenofovir clearance: a pharmacokinetic/pharmacogenetic study on plasma and urines

Abstract: The HIV virus and hepatitis B virus nucleotide reverse transcriptase inhibitor tenofovir has been associated with proximal tubular toxicity; the latter was found to be predicted by plasma concentrations and with single-nucleotide polymorphisms in transporters-encoding genes. A cross-sectional analysis in adult HIV-positive patients with estimated creatinine clearance >60 ml min was performed. Twelve-hour plasma and urinary tenofovir concentrations and single-nucleotide polymorphisms in several transporter-enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…Higher plasma concentration of tenofovir [ 26 , 27 ] and lower patient body weight [ 22 , 28 ] were reported to be associated with TDF-induced KTD. A recent report by Calcagno et al showed that the CC genotype of the ABCC4 4976 was associated with markedly decreased urinary exclusion of tenofovir, although plasma concentration of tenofovir did not differ between different genotypes at ABCC4 4976 [ 29 ]. It is possible that the ABCC4 4976C allele is associated with impaired exclusion of tenofovir into urine, resulting in more concentrated tenofovir in tubular cells, which might lead to KTD in TDF-receiving patients.…”
Section: Discussionmentioning
confidence: 99%
“…Higher plasma concentration of tenofovir [ 26 , 27 ] and lower patient body weight [ 22 , 28 ] were reported to be associated with TDF-induced KTD. A recent report by Calcagno et al showed that the CC genotype of the ABCC4 4976 was associated with markedly decreased urinary exclusion of tenofovir, although plasma concentration of tenofovir did not differ between different genotypes at ABCC4 4976 [ 29 ]. It is possible that the ABCC4 4976C allele is associated with impaired exclusion of tenofovir into urine, resulting in more concentrated tenofovir in tubular cells, which might lead to KTD in TDF-receiving patients.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that NONMMUG034299.1 may be co-transcribed with Cyp3a25 and that NONMMUG034299.1 transcription requires transcriptional machinery independent of Cyp3a25. The transporter Slc28a2, which is a sodium-coupled nucleoside transporter and is particularly important for the uptake of purines and may influence the pharmacokinetics of tenofovir [ 37 ], paired with the lncRNA NONMMUG024460.2, and both transcripts are transcribed from the Watson strand and were co-up-regulated in the absence of gut microbiota. Other examples of PCG paired with a lncRNA include the Phase I drug metabolizing enzymes aldo-keto reductase family 1, member C19 (Akr1c19) and Cyp27a1 (also the rate limiting step in the alternative pathway of bile acid synthesis); the Phase II drug metabolizing enzymes Aldh18a1 and sulfotransferase family, cytosolic, 1C, member 2 (Sult1c2); as well as the metal-binding protein and oxidative stress marker Mt2 (Additional file 2 : Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Urine tests are non-invasive compared to assays that measure plasma. For patients on TFV regimens, the urinary concentration of TFV is usually over 100x more concentrated than in plasma [39]. Also, urine does not require additional sample preparation before testing.…”
Section: Discussionmentioning
confidence: 99%